Innovations in Cell Research and Therapy - Loewy, Zvi (IntechOpen, 2020)
All living things are comprised of cells. A cell is the building block of complex organisms. All cells contain genetic material. Some cells contain subunits known as organelles that perform specific functions. Protein processing, energy generation, and macromolecular biosynthesis are some of the functions of organelles. Recently, advances in cell biology have elucidated new insights in cellular development and the unique functions of different types of cells. The era of biotechnology is rooted in biologics, and cell biology has delivered novel therapeutic candidates. Personalized medicine has its underpinnings in cell biology. Innovations in Cell Research and Therapy focuses on recent key advances that are transforming health and medical sciences. Understanding fundamental cellular processes, including cellular differentiation, the many applications of stem cells, natural and synthetic approaches for inducing apoptosis, and new insights into organelle biology and macromolecular processing are representative examples of the topics that are addressed in the chapters found in this book.